2010
DOI: 10.1163/156853810791069047
|View full text |Cite
|
Sign up to set email alerts
|

Image analysis of the ventral colour pattern discriminates between Spectacled salamanders, Salamandrina perspicillata and S. terdigitata (Amphibia, Salamandridae)

Abstract: In the present study, we applied statistical methods to quantitative image analysis of the persistent and individual ventral colour pattern of Salamandrina salamanders, in order to discriminate between individuals of the two species belonging to this genus. Pictures of 238 individuals from three populations of S. perspicillata and pictures of 95 S. terdigitata from two populations were analysed. Partial least squares discriminant analysis (PLSDA) classified 98.78% of individuals into the correct species. PLSDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…hazard rate) at a given age. Given the results of previous analyses [42][43][44], we allowed recapture probabilities to vary among years. As the study period and number of survey years differ among populations (electronic supplementary material, table S1), the four populations and species were analysed separately.…”
Section: (Iii) Multievent Model For Recruitmentmentioning
confidence: 99%
“…hazard rate) at a given age. Given the results of previous analyses [42][43][44], we allowed recapture probabilities to vary among years. As the study period and number of survey years differ among populations (electronic supplementary material, table S1), the four populations and species were analysed separately.…”
Section: (Iii) Multievent Model For Recruitmentmentioning
confidence: 99%
“…1) the males of S. perspicillata display the throat colour and pectoral girdle coloration or sometimes the whole ventral coloration (during the "stand up" behaviour which was reported for the first time, for salamanders of unknown sex, by Utzeri, Antonelli and Angelini, 2005). Ventral and pectoral coloration of Salamandrina consist of irregular black, red and whitish patches, with patterning differing among individuals (Vanni et al, 1997), among conspecific populations (Costa et al, 2009) and between species (Angelini et al, 2010). It has also been proposed that this coloration could play a role in inter- (Angelini et al, 2010) and intra-specific communication (Costa et al, 2009) although differences of ventral coloration between the sexes were unknown since the method to distinguish the gender in live salamanders was published only recently (Romano, Bruni and Paoletti, 2009).…”
Section: Watchful Behaviourmentioning
confidence: 99%
“…The Volturno River drainage has been identified as a potential contact zone between lineages of both species (Canestrelli et al , 2006 b ). Using image analysis of the ventral coloration patterns, which are unique and are retained throughout the lives of adults, of more than 300 individuals, Angelini et al (2010 b ) showed that the coloration is discriminative and allows for correct assignment of nearly 99% of individuals to their respective species.…”
Section: Introductionmentioning
confidence: 99%